A cross-sectional study on gaming intensity and social vulnerability in adolescents that have a chronic condition - Alexandridis, Dionysis; Nijhof, Sanne L.; van der Rijst, Vincent G.; van der Neut, Damian Y.; Spijkerman, Renske; Stevens, Gonneke W. J. M.; Bakkes, Sander C. J.; Lesscher, Heidi M. B.; van den Eijnden, Regina J. J. M.; van der Ent, Cornelis K.; van den Berg, Gerrit; Peeters, Margot (Frontiers in Public Health, 2023)
Background Adolescents growing up with a chronic condition might experience more social vulnerabilities compared to their healthy peers as an indirect result of their conditions. This can lead to a relatedness need frustration for these adolescents. Consequently, they might spend more time playing video games compared to their peers. Research shows that both social vulnerability and gaming intensity are predictors for problematic gaming. Therefore, we investigated if social vulnerability and gaming intensity are more pronounced in adolescents that have a chronic condition compared to the general population; and if these levels reflect the levels of a clinical group being treated for Internet Gaming Disorder (IGD). Methods Data on peer problems and gaming intensity were compared from three separate samples: a national representative sample of adolescents, a clinical sample of adolescents that are undergoing treatment for IGD, and a sample of adolescents diagnosed with a chronic condition. Results No differences were found on either peer problems or gaming intensity between the group of adolescents that have chronic conditions and the national representative group. The group with chronic conditions scored significantly lower on gaming intensity than the clinical group. No significant differences were found between these groups on peer problems. We repeated the analyses for boys only. Similar results were found for the group with chronic conditions compared to the national representative group. The group with chronic conditions now scored significantly lower on both peer problems and gaming intensity than the clinical group. Conclusion Adolescents growing up with a chronic condition appear similar in their gaming intensity and peer problems compared to their healthy peers.